The Implementation of Industrial Cluster Development Program in Padurenan Village, Kudus - R. Heffi Achid Muharrom; Bambang Supriyono; Khairul Muluk (Wacana Journal of Social and Humanity Studies, 2014)
Small medium enterprise (SME) has a significant contribution to the national economic growth, and the Government has been trying to enhance the competitiveness of SME by using industrial cluster approach.This research tries to discuss the implementation of embroidery and apparel industrial cluster development program in Padurenan Village, Kudus Regency, also to analyze supporting and constraining factors that influence the implementation. The descriptive research method with qualitative approach is used in this research.The result shows that many activities conducted through a synergy among stakeholders have been implemented succesfully and proven to provide a positive impact for the developmet of embroidery and apparel SME in Padurenan. Enhancing the commitment and communication among actors involved in the program are needed for further development.Keywords: Â Embroidery and apparel industry,Â industrial cluster, policy implementation